Implementation of the Canadian C-Spine Rule: prospective 12 centre cluster randomised trial. (29th October 2009) - Stiell, Ian G; Clement, Catherine M; Grimshaw, Jeremy; Brison, Robert J; Rowe, Brian H; Schull, Michael J; Lee, Jacques S; Brehaut, Jamie; McKnight, R Douglas; Eisenhauer, Mary A; Dreyer, Jonathan; Letovsky, Eric; et al.
Abstract : Objective To evaluate the effectiveness of an active strategy to implement the validated Canadian C-Spine Rule into multiple emergency departments. Design Matched pair cluster randomised trial. Setting University and community emergency departments in Canada. Participants 11 824 alert and stable adults presenting with blunt trauma to the head or neck at one of 12 hospitals. Interventions Six hospitals were randomly allocated to the intervention and six to the control. At the intervention sites, active strategies were used to implement the Canadian C-Spine Rule, including education, policy, and real time reminders on radiology requisitions. No specific intervention was introduced to alter the behaviour of doctors requesting cervical spine imaging at the control sites. Main outcome measure Diagnostic imaging rate of the cervical spine during two 12 month before and after periods. Results Patients were balanced between control and intervention sites. From the before to the after periods, the intervention group showed a relative reduction in cervical spine imaging of 12.8% (95% confidence interval 9% to 16%; 61.7% v 53.3%; P=0.01) and the control group a relative increase of 12.5% (7% to 18%; 52.8% v 58.9%; P=0.03). These changes were significant when both groups were compared (P<0.001). No fractures were missed and no adverse outcomes occurred. Conclusions Implementation of the Canadian C-Spine Rule led to a significant decrease in imaging without injuries being missed or patient morbidity. Final imaging rates were much lower at intervention sites than at most US hospitals. Widespread implementation of this rule could lead to reduced healthcare costs and more efficient patient flow in busy emergency departments worldwide. Trial registration Clinical trials NCT00290875 .